2005
DOI: 10.1080/09286580500180598
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of PMMA, Silicone, or Acrylic Intra-Ocular Lenses in Cataract Surgery in Four European Countries

Abstract: Cost-effectiveness ratios of hydrophobic acrylic (Acrysof) were better than those of other types of IOL materials used in most of the countries. Sensitivity analyses were performed to vary the base case analysis to demonstrate the economic importance of the assumptions. In all cases, hydrophobic acrylic IOL material was shown to be a highly cost-effective option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…23,24,[32][33][34][35] In the case of Nd:YAG laser treatment, however, a retrospective design makes it possible to control for observational bias; that is, physicians are not influenced by trial participation and thus the data represent everyday practice. Another limitation is that patient assignment to IOL model was not random, which may have led to selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…23,24,[32][33][34][35] In the case of Nd:YAG laser treatment, however, a retrospective design makes it possible to control for observational bias; that is, physicians are not influenced by trial participation and thus the data represent everyday practice. Another limitation is that patient assignment to IOL model was not random, which may have led to selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Expected-value decision-analysis models provide a useful tool for evaluating the impact of patient characteristics, cost, clinical outcome probabilities, and quality-adjusted life years gained on the cost-effectiveness of a new, relatively unproven technology, especially in the face of uncertainty due to a lack of long-term outcome data 43,44 . Moreover, by identifying the variables that have the greatest impact on cost-effectiveness, these models are valuable for guiding further clinical and laboratory research related to new technologies 45 .…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have reported on the costs associated with spectacles after cataract surgery. 15,[18][19][20][21] A cost-effectiveness analysis (CEA) is considered an important tool in rationalizing health care spending. The CEAs of cataract surgery were mostly expressed as the cost per disabilityadjusted life-years or quality-adjusted life-years gained.…”
Section: Introductionmentioning
confidence: 99%